Decreased plasma motilin concentrations in pregnancy. Issue 6353 (20th November 1982) - Christofides, N D; Ghatei, M A; Bloom, S R; Borberg, C; Gillmer, M D
Abstract : Plasma motilin concentrations were measured in 37 women during the second and third trimester of pregnancy and one week after delivery. The mean plasma motilin concentrations, both fasting and after a glucose load and a mixed meal, were significantly (p less than 0.001) reduced during pregnancy, returning to the normal range one week post partum. Pregnancy appears to have a profound inhibitory effect on plasma motilin, and this may in part be responsible for the gastrointestinal hypomotility associated with pregnancy.